Cepstral Characteristics of Voice in Indian Female Classical Carnatic Singers. - Balasubramanium, Radish Kumar; Shastry, Anuradha; Singh, Mausam; Bhat, Jayashree S. (Journal of Voice, 2015)
Summary Background The cepstral measures are gaining attention in the voice analysis as it is reported to be strong predictor of voice impairments. As singer's voice is reported to be present with more harmonics, it can be hypothesized that there would be an increase in the value of cepstral parameters. Also, little is known about the cepstral characteristics of voices in Indian classical Carnatic singers; and hence, the present study was undertaken with an aim to characterize the singer's voice using cepstral measures. Methods Thirty Indian female classical Carnatic singers and 30 nonsingers participated in the study. Phonation of vowel /a/ was recorded at their habitual pitch and loudness. The cepstral peak prominence and smoothened cepstral peak prominence were analyzed using the Hillenbrand algorithm available in Speech Tool software. Mean and standard deviation was calculated for each group. Obtained scores were analyzed using independent t test. Results Mean raw scores were found to be increased in classical Carnatic singers in comparison with nonsingers. Results of independent t test revealed significant difference between the means of singers and nonsingers for both the cepstral measures at P < 0.05. Conclusions The present study investigated the cepstral characteristic of voice in singers and nonsingers. Results revealed that there was a significant difference between the means of singers and nonsingers indicating that cepstral parameters were higher among the singers in comparison with nonsingers. The obtained results were attributed to the harmonic organization in the voices of singers.